Development of a conceptual success factors model for construction projects: a case of Lithuania - Gudiene, Neringa (2014)
This paper aims to develop a conceptual critical success factors model for construction projects in Lithuania. The concept of success of construction projects and literature review of critical success factors is discussed in the first part. Conceptual model adapted to Lithuania is developed and its elements are described in the second part. Grouped decision-making matrix for the multiple criteria analysis of critical success factors of construction projects is presented at the end of paper.